2019
DOI: 10.1590/1679-78255724
|View full text |Cite
|
Sign up to set email alerts
|

Oblique penetration of tungsten alloy rod to finite-thickness metal plate

Abstract: In order to study the critical ricochet velocity and critical penetration velocity of tungsten alloy rod obliquely penetrating a finite-thickness metal plate, experiment and numerical calculation of tungsten alloy rod impacting on homogeneous armor steel plate with a thickness of 30mm at an angle of 60° were carried out. Compared the experimental and numerical results with the results using models, it is found that, the results of the ricochet models proposed by Tate, Rosenberg and Steven B for semi-infinite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Furthermore, by applying this method, different local cold hardening could be achieved by different total strain. It is necessary to make elongated subcaliber projectiles [ 16 , 17 , 18 , 19 , 20 , 21 ], which are classified as kinetic artillery (KE) projectiles characterized by high kinetic energy related to the area unit of the penetrator cross-section. The depth of penetration of kinetic artillery shells into metallic armored partitions depends on the following factors: the dynamic hardness and density of the shell materials (in this case the core).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, by applying this method, different local cold hardening could be achieved by different total strain. It is necessary to make elongated subcaliber projectiles [ 16 , 17 , 18 , 19 , 20 , 21 ], which are classified as kinetic artillery (KE) projectiles characterized by high kinetic energy related to the area unit of the penetrator cross-section. The depth of penetration of kinetic artillery shells into metallic armored partitions depends on the following factors: the dynamic hardness and density of the shell materials (in this case the core).…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, APFSDS projectiles with carbide-tungsten cores were developed. The development of sintering technology (deployment of such additives as nickel, iron, cobalt, copper, and rhenium) and the mechanical processing of tungsten sinters (e.g., perimeter swaging) made the slenderness of the penetrator increase from 10 to over 30 [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [6] calculated the penetration resistance based on cavity expansion theory and decomposed the penetration process into A and B models, and the penetration equation of each model was presented. Cheng et al [7] studied the critical bounce and penetration velocities of a tungsten alloy rod obliquely penetrating a finite-thickness metal plate. The results showed that the test results were in good agreement with the calculation and numerical results of the critical penetration velocity model proposed by Zhao et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…The velocities of long-rod (monolithic) projectiles, often exceeding 1500 ms À1 , result in a hydrodynamic interaction with armour. 4,5 Cheng et al 5 conducted small-scale experiments using an 11 mm diameter tungsten rod with 90 mm length, fired at velocities around 1300 ms À1 into a 30 mm thick steel plate (also called a witness plate) at an angle of 60°. It was reported that the critical ricochet velocity and ballistic limit were within 100 ms À1 of each other, where tests within this range would lead to the projectile being embedded in the target without penetration.…”
Section: Introductionmentioning
confidence: 99%